Impact of the UK Psychoactive Substances Act on awareness, use, experiences and knowledge of potential associated health risks of novel psychoactive substances. Issue 3 (9th January 2020) - Deligianni, Elena; Daniel, Omari J.; Corkery, John M.; Schifano, Fabrizio; Lione, Lisa A.
Abstract : Aims: The risk of potential harms prompted the UK government to introduce the Psychoactive Substances Act in 2016. The aim of the present study was to evaluate the impact and effectiveness of this new legislation on patterns of novel psychoactive substance (NPS) awareness, use, experiences and risk awareness in a self‐selected sample of UK consumers to inform education and policy. Methods: The Bristol Online Survey was advertised on the Bluelight drug forum and social media Facebook pages and University email between 7 January and 7 February 2015 (168 responses) and 9 March to 18 September 2017 (726 responses). UK country of residence responses were extracted for analysis (SPSS). Results: In a predominantly university‐educated, young (< 25 years) self‐selecting sample, 1 year after introduction of the legislation, NPS use (in males, under 18s, those educated to school/college level, P < .001) has increased, whilst health risk awareness has not changed and remains poor. Users are switching to sourcing NPSs via street dealers (49%) and the darknet (31%) and showing an increase in preference for the herbal NPS Salvia divinorum ( P < .05). The main reasons for NPS use remain the influence of friends (69%) in a social setting and to get high (76%) usually in combination with alcohol, cannabis or ecstasy. Conclusion: Regulation alone, so far, has not impacted on health risk awareness, NPS drug demand and culture in our UK survey sample. Alongside regulation, NPS health promotion education (particularly in schools, colleges) is needed that addresses resilience and both the risks and beneficial effects of NPS.